The game of probability : literature and calculation from Pascal to Kleist - Campe, Rüdiger (Cultural memory in the present., 2012)
There exist literary histories of probability and scientific histories of probability, but it has generally been thought that the two did not meet. Campe begs to differ. Mathematical probability, he argues, took over the role of the old probability of poets, orators, and logicians, albeit in scientific terms. Indeed, mathematical probability would not even have been possible without the other probability, whose roots lay in classical antiquity. The Game of Probability revisits the seventeenth and eighteenth-century ""probabilistic revolution, "" providing a history of the re.